Metal-enhanced fluorescence in liposomes for photothermal studies - Lee, Elizabeth Mei Yin (2013)
Fluorescence has been used in many different fields such as imaging and sensing. Fluorescence self-quenching is a unique property that occurs at high concentrations, resulting in reduced emission intensities. This study aims to demonstrate the emission enhancement of fluorescein encapsulated in liposomes. The emission was observed to be enhanced when gold nanoparticles were added to liposome-encapsulated fluorescein, while quenching effect was still observed for released fluorescein. These effects can then be accounted for in future plasmonic photothermal effect studies.